Anastomotic leakage following cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal cancer: A clinical cohort study - Herzberg, Jonas; Acs, Miklos; Guraya, Salman Yousuf; Schlitt, Hans Jürgen; Honarpisheh, Human; Strate, Tim; Piso, Pompiliu (Surgical oncology, 2024)
Extended oncological resections for colorectal cancer surgery are associated with a high rate of complications, especially anastomotic leakage (AL). This study determines the incidence of risk factors for postoperative complications following cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for colorectal cancer (CRC). In this cohort study, the clinical data of all patients with CRC, treated with CRS and HIPEC, from 2011 to 2021 was analyzed. We considered patients' characteristics, tumor-specific features, postoperative complications, and hospital stay using Chi-Square-test or Fisher's exact test. The Mann-Whitney-U-test was used to measure the probability of differences between two sets of data. Of 1089 HIPEC procedures performed in the study center, 185 patients with CRC and peritoneal metastasis were treated with CRS and HIPEC after formation of at least one anastomosis and therefore included in this study. This included synchronous and metachronous peritoneal metastasis with a mean peritoneal cancer index of 8.67 ± 5.22. In this cohort, AL occurred in 12 (6.5 %) patients. There was no correlation between the number of anastomoses and the occurrence of an AL (p = 0.401). This study reports a low risk of AL after CRS with HIPEC for CRC, comparable to other published data. If a complete cytoreduction seems possible, the risk of anastomotic leakage should not negatively influence the decision to resect. Further studies on this subject are essential to validate our findings. •CRS with HIPEC for colorectal cancer comes with a low risk for anastomotic leakage.•No correlation between number of anastomosis and anastomotic leakage.•No specific risk factor for anastomotic leakage could be found in this cohort.